Polyethylene Glycol (PEG) Induced Drought Stress on Five Rice Genotypes at Early Seedling Stage (Journal of the Bangladesh Agricultural University, 2024)
Drought is a major abiotic stress that restricts the production of crops throughout the world; Bangladesh is not an exception to this. Rice (Oryza sativa L.) as a drought-sensitive crop shows considerable varietal differences towards this environmental stress. With an aim to identify drought tolerant rice variety an experiment was conducted at the Growth Chamber of Plant Physiology Laboratory in the Department of Crop Botany, Bangladesh Agricultural University. Purple rice, Binadhan-8, Binadhan-19, BRRI dhan66 and BRRI dhan71 were evaluated for their drought tolerance during germination and early seedling growth stage. The varieties were tested against four levels of drought stress imposed by Polyethylene glycol 6000 (PEG-6000) @ 0, 5, 10 and 15%. The experiment was laid out in a complete randomized design with three replications. The results showed a gradual decrease in values of all the five varieties towards increasing drought stress of all the considered parameters. The difference in values between control and 5% PEG concentration was not so noticeable but at the highest stress levels the change was dramatic. From the experiment, it can be seen that Purple rice, Binadhan-8 and BRRI dhan66 were considerably tolerant in germination stage towards increasing concentration of PEG and showed better performance in all the considered parameters compared to the other varieties. Overall, these tolerant and sensitive genotypes might be used in the further genetic improvement of the same and different crops.J Bangladesh Agril Univ 18(3): 606–614, 2020https://doi.org/10.5455/JBAU.102585